Metabolomics and water migration analysis provides valuable insights into nutrient generation in Tartary buckwheat (Fagopyrum tataricum) seed germination. Issue 1 (31st December 2022) - Yongliang, Bai; Meiguo, Xin; Roumin, Lin; Weijun, He; Shuyan, He; Rong, Zeng; Yiping, Guo
ABSTRACT: Seed germination of Tartary buckwheat is important for its biological generation of various nutrients. To investigate the nutrient differences during seed germination, the metabolic profiling and moisture status of Tartary buckwheat seed germination were quantitatively measured by ultra-high performance liquid chromatography mass spectrometry (UHPLC-MS) and NMR, respectively. The results showed water was predominantly in free status during the three stages of seed germination divided. Statistical analysis (PCA, OPLS-DA, KEGG) of 53 metabolites at different germination stages revealed the key metabolites of linoleic, flavonoid and phenylalanine biosynthesis during the seed germination. Furthermore, flavonoids biosynthesis was identified as the pathway with the largest difference significance at the second and third stages, while linoleic and phenylalanine metabolisms were screened out as the major pathways with most impact factors in the first and second and the third stage, respectively. The analysis provided valuable insights into the nutrient generation during Tartary buckwheat seeds germination.